PERSEPSI MAHASISWA AKUNTANSI: DETERMINAN YANG MEMPENGARUHI PILIHAN KARIR SEBAGAI AUDITOR - Maria Suryaningsih (STIE Muhammadiyah Jakarta, 2020)
The purpose of this study is to investigate the accounting university students’ perception about the auditors’ ethical orientation, the auditors’ working atmosphere and the auditors’ scandals. The study is also to examine and to analyze the influence of the auditors’ ethical orientation, the auditors’ working atmosphere and of the auditors’ scandals which encompasses the knowledge of general audit at the state-run Indonesian Railway Company (PT KAI) to the assessment of the career choice as an auditor. This study is conducted with the random sampling technique in the data collection. The accounting students of Muhammadiyah University who have studied the auditing or who are still studying the auditing become the population of this study. The data used in this study is the primary data obtained with questionnaires. Meanwhile, the hypothesis test is using the simple regression and multiple regression. There are four hypotheses in this study, all of which are accepted. The result of the test of this hypothesis shows that the ethical orientation, The working atmosphere, and auditors’ scandal, has a significant value of 0,000 The meaning that it has a significant influence to the accounting students’ career choice as an auditor. Andthe results ofthis studyhave theabilityconclusionofall theindependent variables of 76.3% affectthe dependent variableisthe student's career choiceasauditor.